Women and the birth of Russian capitalism : a history of the shuttle trade - Mukhina, Irina, 1979- (NIU Press, 2014)
Little has been known, acknowledged, or studied about the shuttle trade, one of the major manifestations of new Russian life of the 1990s. The term itself seems to suggest something of a rather small scale. Indeed, the amount of each transaction in this trade was miniscule. Individual peddlers traveled to near-abroad with their bulging bags and brought back home for resale only as many goods as they could personally carry in their enormous suitcases. The phenomenon hidden behind the term "shuttle trade" was by no means insignificant or small in scale. By the mid-1990s, it constituted the backbone of Russian consumer trade and was a substantial source of revenue. The primary participants in the shuttle trade were women, and in this enlightening study Mukhina assesses the reasons why women were attracted to this business, the range of the personal experiences of female shuttle traders, and the social impact of women's involvement in this sort of economic activity. By analyzing the social and gendered dimensions of the shuttle trade, the reader can begin to understand more broadly how gender shaped the "transition" period associated with the end of communist regimes in Eastern Europe. Moreover, the difficulties that these women faced highlight the gap between the rhetoric of free market economy and the actual market practices. These women-traders had to create and shape the physical market (an open-air space) for their goods without the basic legislative and other provisions of market economies. The shuttle trade became an avenue of female suffering but also of survival and even empowerment during the time that most Russians now call "the wild 1990s."